2022
DOI: 10.3390/biom12081054
|View full text |Cite
|
Sign up to set email alerts
|

Novel Scaffolds for Modulation of NOD2 Identified by Pharmacophore-Based Virtual Screening

Abstract: Nucleotide-binding oligomerization domain-containing protein 2 (NOD2) is an innate immune pattern recognition receptor responsible for the recognition of bacterial peptidoglycan fragments. Given its central role in the formation of innate and adaptive immune responses, NOD2 represents a valuable target for modulation with agonists and antagonists. A major challenge in the discovery of novel small-molecule NOD2 modulators is the lack of a co-crystallized complex with a ligand, which has limited previous progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Although originally developed for molecular docking screens, DUD-E's decoys are also used as inactives in LBVS [43][44][45][46][47][48] . A recent study showed that the superior enrichment efficiency in convolutional neural network models for SBVS was achieved in the DUD-E dataset because of hidden bias in this dataset rather than a successful generalization of the pattern of protein-ligand interactions 49 .…”
Section: (Ii) Using Dud-e Decoys As Inactivesmentioning
confidence: 99%
“…Although originally developed for molecular docking screens, DUD-E's decoys are also used as inactives in LBVS [43][44][45][46][47][48] . A recent study showed that the superior enrichment efficiency in convolutional neural network models for SBVS was achieved in the DUD-E dataset because of hidden bias in this dataset rather than a successful generalization of the pattern of protein-ligand interactions 49 .…”
Section: (Ii) Using Dud-e Decoys As Inactivesmentioning
confidence: 99%
“…Hydrogen bonds with SER913 and TRP911 were observed in both MDP and a NOD2 agonist. 68 However, MDP forms an additional H bond with ARG857 (interacts with both peptide and carbohydrate part), whereas the inhibitor forms both a hydrogen and a cation-π bond with the same residue. 68 The molecules generated by FOCUS were a mixture of both agonists and inhibitors, as it was observed that there were molecules which formed cation-π bonds with ARG857.…”
Section: Acs Medicinalmentioning
confidence: 99%
“…68 However, MDP forms an additional H bond with ARG857 (interacts with both peptide and carbohydrate part), whereas the inhibitor forms both a hydrogen and a cation-π bond with the same residue. 68 The molecules generated by FOCUS were a mixture of both agonists and inhibitors, as it was observed that there were molecules which formed cation-π bonds with ARG857. Other notable residues include PHE831, TRP911, and ARG857, with ARG857 being significantly involved in hydrogen bonding, enhancing molecular recognition and interaction with ligands.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Guzelj et al described the first modulators of nucleotide-binding oligomerization domain-containing protein 2 (NOD2) identified by virtual screening [9]. NOD2 plays an important role in the development of innate and adaptive immunity because it recognizes bacterial peptidoglycan fragments.…”
mentioning
confidence: 99%